Changes in the morphology of widgeon grass (Ruppia maritima) with the onset of reproduction and impacts on fish assemblages at the Chandeleur Islands, LA - Byrnes, Matthew A.; Darnell, Kelly M.; Darnell, M. Zachary (Frontiers in Environmental Science, 2022)
Seagrass beds are important submerged coastal habitats that support nearshore communities. Ruppia maritima (widgeon grass) is a widespread seagrass species that undergoes dramatic changes in short morphology when reproductive. The goal of this study was to compare fish assemblages associated with reproductive and non-reproductive R. maritima, recognizing the morphological change undergone by the plant when flowering. During the peak reproductive season in August and September 2021, R. maritima meadows at the Chandeleur Islands, LA were sampled to describe the spatial distribution and morphology of reproductive plants and investigate habitat use by fish assemblages. We assessed spatial trends in R. maritima presence and occurrence of reproduction and evaluated differences in shoot morphology. We calculated total fish density, Shannon diversity, and species richness to describe fish assemblages in reproductive and non-reproductive meadows. Additionally, general additive models were used to predict drivers of fish assemblage metrics. Results indicate that R. maritima was distributed along the entire length of North Chandeleur Island, but reproductive plants were located in the central, protected portion of the island. Reproductive plants were more morphologically complex than non-reproductive plants, but this did not drive fish assemblages. Rather, fish abundance was related to R. maritima biomass. This study provides information on patterns and drivers of habitat use by fish in R. maritima-dominated ecosystems that can be used to inform management and restoration.